Introduction to Economics - Dobson, Stephen (Oxford University Press, 1999)
Introducing students to some of the key concepts used by economists, this text shows how to analyze a variety of social and economic issues. Concepts are introduced in the context of real world applications, and many macroeconomic themes are presented in the context of their historical development.